Energy Aware Communication in Wireless Sensor Network: A Survey. (2020) - Parashar, Vivek; Mishra, Bharat; Tomar, G.S.
Abstract: In wireless sensor network (WSNs), sensor nodes are having very limited energy resources, therefore, it is very difficult to deploy sensors at those places where the long lifetime of nodes are required. Hence to increase system lifetime energy efficient circuits and protocols are to be designed. The aim of this study is to present a brief about power consumption by different parts of wireless sensor nodes and various power saving mechanisms deployed at different layers